2010
DOI: 10.3109/07420521003786800
|View full text |Cite
|
Sign up to set email alerts
|

THE CIRCADIAN EXPRESSION OF c-MYC IS MODULATED BY THE HISTONE DEACETYLASE INHIBITOR TRICHOSTATIN A IN SYNCHRONIZED MURINE NEUROBLASTOMA CELLS

Abstract: Circadian clocks govern the mammalian physiology in a day/night-dependent manner. The circadian oscillator of peripheral organs is composed of the same elements as the central pacemaker at the suprachiasmatic nucleus (SCN). The interaction between the circadian clock and several cell cycle components has been established in recent years, since many key regulators of cell cycle and growth control were proved to be rhythmically expressed. In particular, the proto-oncogene c-Myc has been documented to be under ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The present study suggests potential side effects of these small molecules due to disruption of circadian rhythm and derangement of metabolism. In line with this notion, HDAC inhibitors have been shown to alter expression of circadian genes (Repouskou et al 2010; Sanchis-Segura et al 2009). On the other hand, these epigenetic drugs could also be useful in manipulating the circadian rhythm in a beneficial way (Perreau-Lenz et al 2007).…”
Section: Discussionmentioning
confidence: 77%
“…The present study suggests potential side effects of these small molecules due to disruption of circadian rhythm and derangement of metabolism. In line with this notion, HDAC inhibitors have been shown to alter expression of circadian genes (Repouskou et al 2010; Sanchis-Segura et al 2009). On the other hand, these epigenetic drugs could also be useful in manipulating the circadian rhythm in a beneficial way (Perreau-Lenz et al 2007).…”
Section: Discussionmentioning
confidence: 77%
“… 88 90 It has also been shown that there is a circadian clock in N2a cells and that treatments were only effective at specific circadian times. 91 Abnormal and disturbed circadian rhythms are common in AD. 30 , 46 Chronotherapeutic approaches aimed at bolstering weakened circadian rhythms in AD produce beneficial outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of c-Myc in cooperation with loss of function in p53 promotes neoplastic transformation, tumor initiation, maintenance and metastasis 205 . In addition to clock-controlled chromatin remodeling, BMAL1/CLOCK and BMAL1/NPAS2 directly regulate c-Myc transcription via the two E-boxes in the P1 promoter of c-Myc 124,149,206. Disruption of circadian rhythm leads to deregulation of c-Myc which is coupled with increased neoplastic growth in mice, suggesting that the control of G1 cell cycle initiation is one of the key mechanisms for circadian control of tumor suppression 29,124,149 .…”
Section: The Role Of the Mammalian Circadian Clock In Tumor Suppressionmentioning
confidence: 99%
“…Disruption of circadian rhythm leads to deregulation of c-Myc which is coupled with increased neoplastic growth in mice, suggesting that the control of G1 cell cycle initiation is one of the key mechanisms for circadian control of tumor suppression 29,124,149 . Many key cell cycle regulators, such as Cdk4, Itga6, Wnt3, LHx2, Tcf4, Sox 9, Smad7 and Wee1 are also directly regulated at the transcriptional level by BMAL1/CLOCK heterodimer via E-box-mediated interaction in the gene promoters 126,167,206 . p53 and MDM2 are controlled indirectly by the Per genes via the tumor suppressor ataxia-telangiectasia mutated (ATM) at the post-transcriptional level 29,98 .…”
Section: The Role Of the Mammalian Circadian Clock In Tumor Suppressionmentioning
confidence: 99%